Análise das estratégias de internacionalização das maiores instituições financeiras brasileiras no período de 2000 a 2016 - Ferreira, Matheus de Carvalho (2017)
This study aims to analyze the internationalization strategies’ impacts of three large Brazilian financial institutions from the the Dunning Eclectic Paradigm perspective. The methodology was time series analysis through the intervention analysis technique. The study used the data from Banco Central do Brasil from events between the years 2000 and 2016 and analyzed the impacts and magnitude of the Foreign Investment Operations (FDI) operations abroad of the type Mergers and Acquisitions and also greenfield in the strategic guidelines entitled Efficiency Seeking, Markets Seeking and Resources Seeking. It was observed that, most of the investments were considered an intervention, both for mergers and acquisitions of investments in the context of integrated development. It has also been found that the impacts are not only positive for a company and that the investments can have repercussions on more than one strategic approach simultaneously positive or, in some cases, the positive returns obtained in detriment of another. Finally, the study demonstrates relevance of greenfield investments to institutions.